The Role of Digital Literacy in Optimizing Social Media for MSMEs in the Digital Economy Era - Adhi Susano (Institut Teknologi dan Bisnis Semarang, 2024)
In today's rapidly evolving digital landscape, business operators must adeptly understand and evaluate information, particularly in digital formats. Within the realm of social media, digital literacy is indispensable, enabling individuals and organizations not only to utilize these platforms but also to harness them strategically and securely. Proficiency in digital literacy, which includes a comprehensive understanding of various social media features, is crucial for SMEs striving to achieve their business objectives through social media. The impact of digital literacy on social media utilization by SMEs is profound. With robust digital literacy skills, SMEs can refine their marketing strategies, produce compelling content, manage customer interactions efficiently, and safeguard their enterprises from digital threats. Conversely, insufficient digital literacy can hinder SMEs' ability to capitalize on social media opportunities and fully realize their potential. Consequently, advancing digital literacy is vital for SMEs to remain competitive and thrive in today's digital marketplace.